Green human resource management and organizational sustainability / Nurul Hayani Abd Rahman ... [et al.] - Abd Rahman, Nurul Hayani; Ismail, Shaira; Shafie, Nani Ilyana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
In the 21st century, sustainability has become a crucial issue and Green Human Resource Management (GHRM) plays a crucial part in the growth of a company's competitiveness, reputation, and capabilities in the marketplace. The utilization of GHRM in the organizational process creates sustainable business strategies throughout the organization. The awareness that green practices are relevant to corporate sustainability remains low in Malaysia. As the 2016 Global Green Economic Index (GGEI) indicates, Malaysia’s overall performance has been ranked 65th out of 80 countries (Tamanini et al., 2016). The impact of environmental management methods on organizational performance utilizing various metrics is a crucial topic in most studies, although there is little actual evidence to show this (Iraldo et al., 2009; Yang et al., 2010). Previous empirical studies have concluded that if green human resource policies are more robust, more environmental management systems (EMS) will be adopted across different companies (Bohdanowicz et al., 2011). This would lead to a balance between industrial growth and environmental preservation, while still generating more profit (Murari & Bhandari, 2011). Another study also found that the elements of corporate sustainability include green human resource management practices and green intellectual capital. Two selected dimensions of GHRM practices are green recruitment and selection, as well as green rewards. Green intellectual capital is represented by green human capital, green structural capital and green relational capital. These contribute by making a positive impact on a company’s sustainability (Malik et al., 2020).